The Influence of the Amtsal Method on Student Learning Outcomes in Islamic Religious Education Subjects at YWKA Private Vocational School Medan - Putri, Nabillah (Universitas Ibn Khaldun, 2023)
The aim of this research is to determine the effect of the amtsal method on student learning outcomes in the class XI Islamic Religious Education subject, TKJ major at YWKA Medan Private Vocational School. This type of research uses quantitative research. The population in this study was class XI-TKJ I students and class XI-TKJ II students who used 39 samples. The data collection techniques used in this research are observation, tests and documentation.The partial T test results show that the Amtsal Method on the Learning Outcome variable is 0.000 < 0.05 and tcount is 35.414 > 0.361, meaning that the Amtsal Method has a significant effect on the Learning Outcome variable. And the results of the F test (Simultaneous Test) show that Ha is accepted and Ho is rejected, which means that the amtsal method has an effect on student learning outcomes.